Declarative Logic Programming: Theory, Systems, and Applications - Michael, Kifer; Liu, Yanhong (Association for Computing Machinery, 2018)
Logic Programming (LP) is at the nexus of knowledge representation, AI, mathematical logic, databases, and programming languages. It allows programming to be more declarative, by specifying "what" to do instead of "how" to do it. This field is fascinating and intellectually stimulating due to the fundamental interplay among theory, systems, and applications brought about by logic. The goal of this book is to help fill in the void in the literature with state-of-the-art surveys on key aspects of LP. Much attention was paid to making these surveys accessible to researchers, practitioners, and graduate students alike.